KEMAMPUAN ANTIFUNGI EKSTRAK RIMPANG TEMULAWAK (Curcuma xanthorrhiza) TERHADAP Candida albicans - Novianti, Dewi (Faculty of Mathematics and Natural Science, Universitas PGRI Palembang, 2016)
Candida albicans yeast is a normal microflora of the human body are pathogenic if the amount is excessive and decreased immune system. In general infections caused by C.albicans called candidiasis. People use ginger rhizome (Curcuma xanthorrhiza) for traditional treatment of various diseases including disease whitish and sprue. Research purposesÂ to test the ability of ginger rhizome extract antifungal against C. albicans. This study was conducted in August 2016 until October 2016 held at the Laboratory of Microbiology and Biotechnology, Integrated Laboratory PGRI Palembang University. This study uses a completely randomized designÂ with six treatments using ginger rhizome extract concentration and performed four replications for each treatment. From the research that has been conducted shows that the methanol extract of ginger rhizome has the ability antifungal against Candida albicans in vitro, a concentration of 10% methanol extract of ginger rhizome produce inhibition zone diameter of 16.2 mm.Keywords: Extract, ginger rhizome, antifungal, Candida albicans.ABSTRAKJamur Candida albicans merupakan mikroflora normal tubuh manusia bersifat patogen jika jumlahnya berlebihan dan daya tahan tubuh menurun. Secara umum infeksi yang disebabkan oleh C.albicans disebut kandidiasis. Masyarakat memanfaatkan rimpang temulawak (Curcuma xanthorrhiza) untuk pengobatan tradisional berbagai penyakit diantaranya keputihan dan sariawan.Tujuan penelitian untuk menguji kemampuan antifungi ekstrak rimpang temulawak terhadap C. albicans. Penelitian ini dilaksanakan pada bulan Agustus 2016 sampai dengan Oktober 2016 bertempat di Laboratorium Mikrobiologi dan Bioteknologi, Laboratorium Terpadu Universitas PGRI Palembang. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) dengan menggunakan 6 perlakuan konsentrasi ekstrak rimpang temulawak dan dilakukan 4 kali ulangan pada tiap perlakuan. Dari penelitian yang telah dilakukan didapatkan bahwa ekstrak metanol rimpang temulawak mempunyai kemampuan antifungi terhadap Candida albicans secara in vitro, konsentrasi 10% ekstrak metanol rimpang temulawak menghasilkan diameter zona hambat sebesar 16,2 mm.Â Kata Kunci: ekstrak, rimpang temulawak, antifungi, Candida albicans